Effects of Physical Properties and Environmental Conditions on the Natural Dispersion of Oil - Chenfang Wang; Longxi Han; Yi Zhang; Anqi Jiang; Jie Wang; Xiangming Niu (Journal of Marine Science and Engineering, 2023)
The natural dispersion of oil depends on the oil types, wave-mixing energy, and the temperature and salinity of water. Laboratory experiments were conducted to investigate the effects of these factors on oil dispersion. The results demonstrated that the increase in temperature significantly enhanced the oil dispersion efficiency, particularly for low-viscosity oils. At 30 °C, the dispersion efficiency is 2 times higher than that at 15 °C, while salinity has no significant effect on dispersion efficiency. Nonlinear fitting results revealed an exponential increase in dispersion efficiency with the energy dissipation rate. Furthermore, partial correlation analysis was employed to examine the effects of oil density, viscosity, and surface tension on dispersion efficiency. The results indicated a high correlation between density, viscosity, and dispersion efficiency (r = −0.801, r = −0.812), whereas the correlation coefficient of surface tension was low (r = −0.286). Based on these findings, linear and nonlinear regression models were established between dispersion efficiency and density and viscosity, enabling a rough estimation of oil spill dispersion efficiency under low sea state conditions.